Updated Integrated Framework for Making Clinical Decisions Across the Lifespan and Health Conditions. Issue 3 (5th January 2022) - Deutsch, Judith E; Gill-Body, Kathleen M; Schenkman, Margaret
Abstract: The updated Integrated Framework for Clinical Decision Making responds to changes in evidence, policy, and practice since the publication of the first version in 2008. The original framework was proposed for persons with neurological health conditions, whereas the revised framework applies to persons with any health condition across the lifespan. In addition, the revised framework (1) updates patient-centered concepts with shared clinical decision-making; (2) frames the episode of care around the patient's goals for participation; (3) explicitly describes the role of movement science; (4) reconciles movement science and International Classification of Function language, illustrating the importance of each perspective to patient care; (5) provides a process for movement analysis of tasks; and (6) integrates the movement system into patient management. Two cases are used to illustrate the application of the framework: (1) a 45-year-old male bus driver with low back pain whose goals for the episode of care are to return to work and recreational basketball; and (2) a 65-year-old female librarian with a fall history whose goals for the episode of care are to return to work and reduce future falls. The framework is proposed as a tool for physical therapist education and to guide clinical practice for all health conditions across the lifespan.